PERANAN PENYULUH PERTANIAN PADA KELOMPOKTANI DALAM MENSUKSESKAN UPSUS PADI SRI (SYSTEM OF RICE INTENSIFICATION) DI KECAMATAN KEPANJEN KABUPATEN MALANG (STUDI KASUS PADA KELOMPOKTANI UTAMA 1 DI DESA KEMIRI) - Gori, Gregorius; Mutiara, Farah; Suwasono, Son (Fakultas Pertanian, 2019)
The condition of Indonesia's food security in 2017 is getting worse, due to the shifting function of agricultural land in Indonesia. FAO (Food and Agriculture Organization) posted, Indonesia is on a serious level in the global hunger index. In 2015 the government wanted to repeat the golden period with a Special Effort Activity (UPSUS) to Increase Rice, Corn, Soybean (PAJALE) Production in 2015. The role of agricultural extension agents in the success of UPSUS PAJALE requires quality HR (Human Resources) as the main capital for become the actor or driver of development in an area. One of the systems carried out by the PAJALE UPSUS Program is SRI (system of Rice Intensification). SRI (System of Rice Intensification) is a rice cultivation technique that is able to increase rice productivity by changing the management of plants, soil, water, and nutrients. The purpose of this study is to describe the role of field agricultural instructors in applying the SRI (System of Rice Intensification) rice system in Kemiri Village, Kepanjen District, Malang Regency, the analytical method used is qualitative descriptive. The role of the field agriculture instructor (PPL) through the Soybean Maize Rice Special Program (UPSUS PAJALE) plays an important role in carrying out all program activities. This is seen in each of its roles, where the role of extension agents as facilitators is in terms of fostering members of farmer groups, the role of extension agents as organizers in each extension activity, the role of extension agents as dynamics namely in activating farmer group activities, the role of extension agents as technicians namely in extension provide technical knowledge, the role of extension agents as mediators, namely the information link aspect. Kondisi ketahanan pangan pada tahun 2017 ini semakin memburuk, dikarenakan beralih fungsinya lahan pertanian di Indonesia. FAO (Food and Agriculture Organisation) memposting, Indonesia berada di level serius dalam indeks kelaparan global. Pada tahun 2015 pemerintah ingin kembali mengulang masa emas itu dengan Kegiatan Upaya Khusus (UPSUS) Peningkatan Produksi Padi, Jagung, Kedelai (PAJALE) tahun 2015. Peranan penyuluh pertanian dalam mensukseskan UPSUS PAJALE membutuhkan SDM (Sumber Daya Manusia) yang berkualitas sebagai modal utama untuk menjadi pelaku atau penggerak pembangunan di suatu daerah. Salah satu sistem yang dilakukan Program UPSUS PAJALE yaitu SRI (system of Rice Intensification). SRI (System of Rice Intensification) adalah teknik budidaya tanaman padi yang mampu meningkatkan produktivitas padi dengan cara mengubah pengelolaan tanaman, tanah, air, dan unsur hara. Tujuan penelitian ini yaitumendeskripsikan peran penyuluh pertanian lapangan dalam menerapkan sistem padi SRI (System of Rice Intensification) di Desa Kemiri, Kecamatan Kepanjen, Kabupaten Malang, metode analisis yang digunakan yaitu deskriptif kualitatif. Peran Penyuluh Pertanian lapangan (PPL) melaui Program Khusus Padi Jagung Kedelai (UPSUS PAJALE) ini sangat berperan di dalam melalukan seluruh kegiatan program. Hal ini dilihat dalam setiap perannya, sebagai organisator yaitu sebagai penyelenggara pada setiap kegiatan penyuluhan, peran penyuluh sebagai dinamisator yaitu dari segi mengaktifkan kegiatan kelompoktani, peran penyuluh sebagai teknisi yaitu segi penyuluh dalam memberikan pengetahuan teknis, peran penyuluh sebagai mediator yaitu segi penghubung informasi.